Fine wares from the excavations of the late Roman fort at Ulmetum (province of Scythia): Chronology of the late 4th and 5th century main contexts - Băjenaru, Constantin (Rei Cretariae Romanae Fautorum Acta, 2022)
The fine pottery collected from the habitation layers of the first period of the fortification at Ulmetum (c. 380/390–470/480 AD) benefits from a very good absolute. chronology, based on the association with rich numismatic material. Varying amounts of penetration of African, Asia Minor and Pontic vessels are noticeable in this important military site in the province of Scythia. Products with limited regional or local distribution are also present.